2013
DOI: 10.5001/omj.2013.92
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Intravenous Fentanyl on Pain and Duration of the Active Phase of First Stage Labor

Abstract: Fentanyl provides good analgesic effect for pain management during labor by considerably reducing the duration of the active phase, and can therefore be used as an acceptable analgesic agent during labor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 14 publications
2
8
0
2
Order By: Relevance
“…However, the explanation for the conflicting findings between subgroups for PONV is less clear. When fentanyl is administered intravenously, the time to peak effect is short (3‐5 minutes) because of rapid passage across the blood‐brain barrier, and the duration of action is also short (45‐60 minutes) because of rapid redistribution . Considering these pharmacokinetic properties, the period of maximum effect of the fentanyl administered immediately after surgery could overlap with the anesthesia recovery period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the explanation for the conflicting findings between subgroups for PONV is less clear. When fentanyl is administered intravenously, the time to peak effect is short (3‐5 minutes) because of rapid passage across the blood‐brain barrier, and the duration of action is also short (45‐60 minutes) because of rapid redistribution . Considering these pharmacokinetic properties, the period of maximum effect of the fentanyl administered immediately after surgery could overlap with the anesthesia recovery period.…”
Section: Discussionmentioning
confidence: 99%
“…When fentanyl is administered intravenously, the time to peak effect is short (3-5 minutes) because of rapid passage across the blood-brain barrier, and the duration of action is also short (45-60 minutes) because of rapid redistribution. 24,25 Considering these pharmacokinetic properties, the period of maximum effect of the fentanyl administered immediately after surgery could overlap with the anesthesia recovery period. Hence, it is hypothesized that the higher incidence of PONV in the subgroup with fentanyl administered at the end of surgery was due to longer exposure to the maximum effects of the drug.…”
Section: Discussionmentioning
confidence: 99%
“…Using the sealed envelope technique, parturients were randomly allocated to seven study groups: normal saline (control), low‐dose meperidine (0.5 mg/kg), high‐dose meperidine (0.75 mg/kg), low‐dose fentanyl (0.5 mcg/kg), high‐dose fentanyl (0.75 mcg/kg), low‐dose tramadol (0.5 mg/kg) and high‐dose tramadol (0.75 mg/kg). The doses of the study drugs were well below the recommended levels for shivering treatment and postoperative pain management in cesarean delivery patients . Parturients presenting with shivering before delivery, temperatures greater than 38°C or less than 36°C, and those with contraindications to spinal anesthesia and narcotics were excluded from the study.…”
Section: Methodsmentioning
confidence: 99%
“…Twelve studies were selected for the meta-analysis by following the inclusion and exclusion criteria (Tables 1 and 2) [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36]. A flow diagram of literature retrieval, screening, and study selection process is presented in Figure 1.…”
Section: Studies Selectionmentioning
confidence: 99%
“…Epidural analgesia has been shown to reduce the active phase of first stage of labor [28] as well as increasing the risk of prolonged first and second stage of labor [29][30][31][32][33][34][35][36]. Interestingly, the present study found that use of epidural analgesia can prolong the duration of first stage of labor in primigravid women by 2.66 min and does not prolong the second stage of labor SMD 2.66, (95%CI: 0.89, 4.43, p<0.00001, Z=2.95).…”
Section: Total (95% Ci)mentioning
confidence: 99%